Kemitraan Indonesia-Australia dalam Mengimplementasi Pengarusutamaan Gender di Indonesia (Studi Kasus Pelaksanaan Program MAMPU di Kabupaten Lombok Timur) - Mariah Mariah; Ismah Rustam; Y. A. Wahyudin (Indonesian Journal of Global Discourse, 2022)
This research aims to analyze the gender issues and implementation of gender mainstreaming through the MAMPU program in East Lombok Regency, West Nusa Tenggara Province. In addition, this research uses the qualitative approach, with a case study approach, while the type of data used in this research is derived from a combination of primary and secondary sources; namely through observation, interview and documentation. This research also uses Miles & Huberman’s interactive model of data analysis. Furthermore, this research uses the Gender Theory, limiting it to the scope of International Relations and Gender Mainstreaming, thus combining it as one conceptual framework. The research concludes that the implementation of the MAMPU program has provided positive results in helping victims of gender-related issues such as household abuse and child marriages.